Practical solutions for overcoming artificial disulfide scrambling in the non-reduced peptide mapping characterization of monoclonal antibodies - Andrew Kleinberg; Yuan Mao; Ning Li (mAbs)
Non-reduced peptide mapping provides essential data for characterizing therapeutic monoclonal antibodies by isolating disulfide connections between specific cysteines. However, conventional digestive strategies used throughout the biopharmaceutical industry have been shown to cause unintentional rearrangement of disulfide connections (disulfide scrambling), thus generating connectivity profiles that do not accurately represent the protein being analyzed. Common misconceptions (e.g. avoiding basic-pH digestion to prevent disulfide scrambling) have led to the development of alternative reagents and conditions that can alleviate this issue, but yield problematic digestion profiles. Herein, we systematically and comprehensively examine the primary considerations for accurate non-reduced peptide mapping, and provide effective, practical solutions to minimize undesired behavior while still yielding high-quality digests. Additionally, we present a method that exploits intentional disulfide scrambling as a reference tool to demonstrate the robustness of our proposed strategies. We also introduce maleimide as a cysteine-alkylating reagent and demonstrate its benefits over industry-leading analogs such as N-ethylmaleimide in terms of compatibility with regulatory reports.